The concept of human organs and tissues with reference to transplantation: lessons from international law - Krishtal, Viktoriya V. (Journal of the Belarusian State University. International Relations, 2022)
The definition of the term “human organs and tissues” is considered with reference to the transplantation of organs and tissues. We review the doctrinal approaches, provisions of international legal acts, international instruments, and national legal frameworks related to the transplantation of human organs and tissues. We conclude by proposing a definition of the terms “human organ” and “human tissue” with emphasis on the substantive aspects inherent in them.
Keywords: human organ; human tissue; transplantation; Oviedo convention; World Health Organisation; Council of Europe; European Union; Commonwealth of Independent States; Eurasian Economic Union